A tipografia como manifestação cultural - Mendonça, Ismael Lopes (2018)
This work analyzes the typography and the cultural manners as times have perceived it, not only as a system producing series of texts, but the purposes ascribed to the aesthetics of the characters and the compositions. It highlights the dynamic nature of the construction of mean-ings that interact with men beyond mechanical operations and verbal representations. It also reflects the ordering marks in the typographic symbolisms, expressed in their cultural regimes of information. Dealing with this informational complexity is the main objective of this re-search carried out in the master's degree of Information Science at Federal University of Ceará. It relies on the social epistemology of the field to understand typography in a way not restricted to physical and cognitive dimensions, but as a complex and relatable phenomenon to socially constructed ordinations and meanings. For that, it uses anthropological and herme-neutical assumptions which have been used by this field to update its object of study, which are the notions of cultural mediation, neodocumentation and information regime. As an em-pirical experiment, we opted to analyze the graphic design of the special notebooks produced by the Ceará newspaper O Povo and the winners of the Esso Journalism Award in the catego-ry of graphic creation for the newspaper Planeta seca (2012) and Sertão a ferro e fogo (2014). These are thematic and investigative journalistic productions linked to the imaginary of the northeastern backlands. These documents and their typographic symbolisms were interpreted by the bias of their production process and by the professionals who sign their content, using the hermeneutic-dialectical method and the interview and participant observation techniques. This study of exploratory, qualitative and documentary nature made it possible to understand the objects as infocommunicational phenomena resulting from social practices operated in the newspaper environment. Thus, they become dynamic codes of interaction, in which mediators play an active role in constructing unusual readings, hybrid narratives that relate to a diversity of contexts and identities. In addition, its production process marks and at the same time con-ditions the communication team and enterprise, which are now publicly recognized for this type of relationship with information. It is concluded that these special notebooks and their typographies integrate complex cultural and informational categories, by which they become illustrative phenomena for the social paradigm of Information Science. This finding favors the line of contemporary research in this field and its interdisciplinary tradition.